Assemblages of stream amphibian communities at Gunung Jagoi, Bau District, Sarawak - Tham, Chook Yan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study attempts to determine the diversity and similarity of amphibians at three different streams at Gunung Jagoi, western Sarawak (Borneo). The broad aims of the study were to compare the species diversity, species richness and similarity of amphibians at different streams, and to produce an inventory of amphibians of the site. Field work was conducted between November 2011 to February 2012, and each site had 4 nights of data. The streams are at different elevations and differ in dimensions and other characteristics such as stream width and stream flow velocity. The position of capture for each frog collected was recorded and coded. Data on species diversity, species richness and similarity of anuran amphibians at three streams of Gunung Jagoi were collected, and computed using EstimateS V8.2, to determine diversity, species richness and species similarity. There is no literature on the diversity of amphibians at Gunung Jagoi, hence this study provided the first inventory of frogs at this locality. Additionally, it presents new ecological information on several amphibian species. A total of 17 species from 11 genera and six families were recorded. The species accumulation curves of the three study sites reveal that an asymptote is not achieved,indicating that more sampling efforts are required. Different in microhabitat parameters can affect the assemblages and overlap of the frog species. Hylarana raniceps was found to be one of the generalist that can be seen in all the study sites with different characteristics. Some species were seen to share the similar microhabitat, different microhabitat parameters can split out the species based on their ecological requirement.